2018
DOI: 10.20944/preprints201808.0328.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial Distribution of DDT and Its Metabolites in Soils from Indoor Residual Spraying in Tshilamusi Village, Limpopo

Abstract: The continued application of organochlorine pesticides (OCPs) in indoor residual spraying has posed significant threat to human health in Northern part of South Africa, despite its ban. In this study, we investigated the occurrence and spatial distribution of DDTs and its metabolites in surface soil (30 samples) collected in and around the spray homesteads; demarcated into three concentric zones A, B, C in Tshilamusi Vhembe district, South Africa. DDTs were the most abundant of all the OCPs chemicals found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The contamination of these plants is likely to be as a result of root uptake of DDT residues and its metabolites present in the soil, as opposed to aerial precipitation of DDT during IRS (Van Dyk et al, 2010). The high mean levels of DDE and DDD detected in vegetable samples from the study areas were not significantly different (p > 0.05) from the mean levels of DDE and DDD in vegetable samples from the control site, probably because similar plant tissues are capable of absorbing insecticides (Gitari et al, 2018;Ngabirano and Birungi, 2021) at the same rate. ∑DDT levels from the current study were however lower than those reported by Van Dyk et al (2010) of 43 μgkg -1 in vegetables from Vembe district S. Africa, two months after IRS of DDT.…”
Section: Levels Of Ddt Residues In Leafy Vegetablesmentioning
confidence: 80%
See 1 more Smart Citation
“…The contamination of these plants is likely to be as a result of root uptake of DDT residues and its metabolites present in the soil, as opposed to aerial precipitation of DDT during IRS (Van Dyk et al, 2010). The high mean levels of DDE and DDD detected in vegetable samples from the study areas were not significantly different (p > 0.05) from the mean levels of DDE and DDD in vegetable samples from the control site, probably because similar plant tissues are capable of absorbing insecticides (Gitari et al, 2018;Ngabirano and Birungi, 2021) at the same rate. ∑DDT levels from the current study were however lower than those reported by Van Dyk et al (2010) of 43 μgkg -1 in vegetables from Vembe district S. Africa, two months after IRS of DDT.…”
Section: Levels Of Ddt Residues In Leafy Vegetablesmentioning
confidence: 80%
“…The vegetable samples from the villages in the study districts were mainly contaminated with the insecticide residues in the order DDE > DDT > DDD. G. gynandra, A. esculentus, and S. melongena were the most contaminated vegetables in both study areas and the control site, probably because the plants have abilities to absorb the residues into their tissues in a short time (Gitari et al, 2018). The contamination of these plants is likely to be as a result of root uptake of DDT residues and its metabolites present in the soil, as opposed to aerial precipitation of DDT during IRS (Van Dyk et al, 2010).…”
Section: Levels Of Ddt Residues In Leafy Vegetablesmentioning
confidence: 96%